STRATIGRAPHY AND FUSULINIDS OF THE KASIMOVIAN AND LOWER GZHELIAN (UPPER CARBONIFEROUS) IN THE SOUTHWESTERN DARVAZ (PAMIR) - Leven E.J.; Davydov V.I. (My University, 2001)
A detailed fusulinid biostratigraphic zonation of the Kasimovian and lowermost Gzhelian in southwestern Darvaz is proposed. Based on the investigation of five stratigraphic sections, five local fusulinid zones were established. These zones correlate with their chronostratigraphic equivalents in the East-European Platform and in the Urals, Arctic and Carnic Alps regions. Eighty-seven species and subspecies, which belong to 18 genera and 7 families of fusulinids, were identified in the Kasimovian and lowermost Gzhelian of Darvaz. Among them, two genera (Kushanella and Darvasoschwagerina), one subgenus (Tumefactus), and 24 species are new ( i. e. Fusiella segyrdashtiensis, Quasifusulina pseudotenuissima, Protriticites putrjai, P. compactus, Obsoletes darvasicus, Schwagerinoides (Schwagerinoides) pamiricus, Schw. (Tumefactus) oblisus, Montiparus kushanicus, M. rauserae, M. pigmaeus, M. memorabilis, M. citreus, M. hirsutus, M. dubius, M. stuckenbergiformis, M. desinens, Triticites umbonoplicatiformis, T. licis, Rauserites concinnus, R. jucundus, R. darvasicus, Kushanella globosa, K. insueta, Darvasoschwagerina donbasica).
Keywords: Carboniferous; Gzhelian; Kasimovian; Fusulinids; Stratigraphy; Paleontology; Central Asia; Paleozoic::Carboniferous::Pennsylvanian::Upper::Kasimovian; Палеозой::Каменноугольная; Палеозой::Каменноугольная::Верхний::Гжельский; Палеозой::Каменноугольная::Верхний::Касимовский; Paleozoic::Carboniferous; Paleozoic::Carboniferous::Pennsylvanian::Upper::Gzhelian